Frostbite among Iraqi soldiers during Iraqi-Iranian war - Al-Ani, Nafi A. O. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Frostbite is a cold weather injury characterized by tissue freezing. It can adversely impact military operations. This study was carried out to demonstrate thefrostbite among Iraqi -Iranian war.Materials: The over surveillance period was 1st Dec. 1987 to 1st March 1988. A form was tilled for each affected soldier. All cases were followed till Dec. 1988.Results: The reported frostbite cases were 10 000 cases. The rate was of 100 cases per 100 000 person - year. The foot was the most affected site. High frostbite cases were reportedduring the active military operations.Conclusion: Education, acclimatization and strict enforcement of cold weather injury preventive measures arc necessary in military services.